COVID-19 outbreak impact on urolithiasis treatments: A multicenter retrospective study across 9 urological centers in Italy - Mazzon, Giorgio; Ferretti, Stefania; Serafin, Emanuele; Claps, Francesco; Acquati, Pietro; Brusa, Davide; Germinale, Federico; Celentano, Giuseppe; Pescuma, Andrea; Fugini, Andrea Vismara; Campobasso, Davide; Maestroni, Umberto; et al. (Current urology, 2024)
Abstract Background The coronavirus disease (COVID-19) pandemic has posed challenges to the global health care community, affecting the management of upper urinary tract stones. Materials and methods This retrospective study involved 9 Italian centers. We compared the 12-month period prior to COVID-19 (March 1, 2019, to February 28, 2020; Period A) with the COVID-19 period (March 1, 2020, to February 28, 2021, Period B). This study aimed to compare outcomes during Periods A and B, specifically focusing on the overall number of treatments, rate of urgent/elective cases, and operational complexity. Results A total of 4018 procedures were collected, comprising 2176 procedures during Period A and 1842 during Period B, indicating a loss of 15.35% (p < 0.001). In the elective cases, 1622 procedures were conducted in Period A, compared with 1280 in Period B, representing a 21.09% reduction in cases (p = 0.001). All types of stone treatments were affected: extracorporeal shock wave lithotripsy (−29.37%, p = 0.001), percutaneous nephrolithotomy (−26.47%, p = 0.008), retrograde surgeries for renal stones (−10.63%, p = 0.008), and semirigid ureterolithotripsy (−24.86%, p = 0.008). Waiting lists experienced significant delays during Period B. The waiting time (WT) for elective procedures increased during Period B (p < 0.001). For ureteral stones, the mean WT in Period A was 61.44 days compared with 86.56 days in Period B (p = 0.008). The WT for renal stones increased from 64.96 days in Period A to 85.66 days in Period B for retrograde intrarenal surgery (p = 0.008) and from 96.9 days to 1103.9 days (p = 0.035) for percutaneous nephrolithotomy procedures. Conclusions Our study demonstrates that COVID-19 significantly disrupted endourological services across the country. Our data underline how patients received treatment over a prolonged period, potentially increasing the risk of stone-related complications and patient discomfort.